Comprehensive utilization method of vanadium, heat energy, vanadium recovery process neutral dregs and tailings in low heating value stone coal vanadium ores - XU YONGXIAN; REN JIANGUO; FENG ZHIMIN; WANG XICHANG; SHE ZONGHUA; HAN QILEI; LIANG BAOPING; LIU GUOZHENG; WAN HONGQIANG; WANG WENJUAN; GUO YOUQIAN; XING JIGUANG; et al. (2016)
The invention discloses a comprehensive utilization method of vanadium, heat energy, vanadium recovery process neutral dregs and tailings in low heating value stone coal vanadium ores. The stone coal vanadium ores are subjected to whole-wet vanadium recovery directly through a coarse particle normal temperature low acid pre-activation technology; the ores do not need to be subjected to roasting or fine grinding, so that the equipment investment and the vanadium recovery cost are greatly lowered; meanwhile, leached residues mainly contain the oxides of silicon, calcium, magnesium, iron and the like after being combusted for power generation by a novel circulating fluidized bed boiler so as to be suitable for being used as raw materials of baking-free bricks; and the leached residues, vanadium recovery process neutral dregs, part of fine stuff and cement are used for manufacturing the baking-free bricks, so that the vanadium, the heat energy, siliceous gangues and the like in the ores are fully utilized. Accord